EVALUASI KONDISI TERUMBU KARANG DI TELUK KULISUSU MUNA SULAWESI TENGGARA - Suharyanto Suharyanto; Utojo Utojo (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The objective of this research was to know the condition of coral reef in Kulisusu Bay of Muna. Field observation with scuba diving apparatus was done in February 29th, 2000 located in 3 stations and within the depth of 3 to 10 m. Line intercept transect method was used along 100 m of plastic rope. The data of coral reef were analysed by using dBase III+ and Lifeform packet program. The result showed that coral reef condition in two stations were generally in good condition. Fair condition was observed only in station I. The life coral reef was dominated by hard coral Acropora, namely Acropora branching, Acropora Encrusting, Acropora Submassif, Acropora digitate, and Acropora tabulate. While non Acropora namely coral branching, coral encrusting, coral foliose, and coral massive, Milepora and Heliopora were found acrros the coral reef. On the other hand the most abudance benthic fauna were mainly dominated by sponge and soft coral.